Successful Nonsurgical Treatment of Pneumomediastinum, Pneumothorax, Pneumoperitoneum, Pneumoretroperitoneum, and Subcutaneous Emphysema following ERCP - L. Fujii; A. Lau; D. E. Fleischer; M. E. Harrison (Gastroenterology Research and Practice)
Complications related to endoscopic retrograde cholangiopancreatography (ERCP) include pancreatitis, hemorrhage, cholangitis, and perforation. ERCP-related perforation is uncommon, but mortality rates are high. Diagnosis requires a high clinical suspicion for early detection to allow optimal management of the perforation and a better prognosis. Treatment depends on the location and mechanism and increasingly involves nonoperative management. We report a case of successful nonsurgical treatment of a patient with extensive air involving the peritoneum, retroperitoneum, thorax, mediastinum, and subcutaneous tissues following an ERCP perforation.